2021
DOI: 10.1002/hbm.25643
|View full text |Cite
|
Sign up to set email alerts
|

Coherent neural oscillations inform early stroke motor recovery

Abstract: Neural oscillations may contain important information pertaining to stroke rehabilitation. This study examined the predictive performance of electroencephalography‐derived neural oscillations following stroke using a data‐driven approach. Individuals with stroke admitted to an inpatient rehabilitation facility completed a resting‐state electroencephalography recording and structural neuroimaging around the time of admission and motor testing at admission and discharge. Using a lasso regression model with cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 80 publications
(131 reference statements)
3
24
1
Order By: Relevance
“…Increased TotCoh following tDCS might correlate with the timing of recovery; indeed, higher speed of motor improvement was consistently observed in all behavioral tests in tDCS-stimulated stroke mice, whereas sham-stimulated stroke mice showed slower spontaneous recovery accompanied by lower values of TotCoh. Our contention is in agreement with recent clinical studies, 19,38–41 demonstrating correlations between functional abnormalities of brain networks and poststroke clinical outcomes and suggesting that connectivity changes at baseline (ie, in days immediately following stroke) could be used as a predictive index of stroke recovery (measured by specific scales used clinically in stroke).…”
Section: Discussionsupporting
confidence: 92%
“…Increased TotCoh following tDCS might correlate with the timing of recovery; indeed, higher speed of motor improvement was consistently observed in all behavioral tests in tDCS-stimulated stroke mice, whereas sham-stimulated stroke mice showed slower spontaneous recovery accompanied by lower values of TotCoh. Our contention is in agreement with recent clinical studies, 19,38–41 demonstrating correlations between functional abnormalities of brain networks and poststroke clinical outcomes and suggesting that connectivity changes at baseline (ie, in days immediately following stroke) could be used as a predictive index of stroke recovery (measured by specific scales used clinically in stroke).…”
Section: Discussionsupporting
confidence: 92%
“…Of note, a recent paper (which was not part of our database since its publication was after our search end date) has highlighted a prominent role of coherence, rather than power, in predicting early motor recovery after acute stroke. Specifically, only the low beta band recorded on M1 demonstrated negative associations with motor recovery, highlighting the maladaptive nature of beta coherence between ipsilesional M1 and ipsilesional parietal and controlateral temporal and supplementary motor area in early stroke recovery (Cassidy et al 2021 ). Interestingly, another work of the same group (not found by the research strategy used) showed that delta band coherence with ipsilesional M1 was related to greater injury and poorer motor status in a subacute timeframe (Cassidy et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, significant decrease in alpha coherence (connectivity) involving regions overlying anterior frontal cortex negatively correlated with self-agency. Past work demonstrating the involvement of neural oscillations in the alpha frequency band in stroke recovery (107,108) encourage additional work to validate these findings in a stroke cohort.…”
Section: Neural Correlates Of Self-efficacymentioning
confidence: 89%